Towards a Sociology of Fashion Micro-Enterprises: Methods for Creative Economy Research. (October 2016) - McRobbie, Angela
This article argues that the emerging field of creative industry studies, for reasons of its inter-disciplinary origins, has tended to sidestep questions of method. Sociology can play a role in rectifying this deficit for three reasons; first, the long-standing attention to qualitative, interview and observation-based research is useful, especially for scholars investigating the experience of work and labour in the creative sector, second because recent sociological attention to the whole terrain of big data has repercussions even for small-scale studies such as the one outlined here, and third because well-known sociological studies of creative professionals offer value and insight into the conduct of re-differentiated cultural sectors, in this case fashion design. By providing details of a funded study of this sector in three cities (London, Berlin and Milan), the article also proposes a utilising of the recent role of the so-called entrepreneurial university as creative hub, so as to develop a more radical idea of 'knowledge transfer'. In addition, the article encourages a two-way exchange between sociology and creative industry studies to develop a better understanding of cultural goods, items and works of art. Such a focus on the material object or outcome of creative practice also opens up the possibility for a more collaborative exchange with the cultural producers.